Routledge handbook on science in the Islamicate world
1 online resource
Keywords: "The Routledge Handbook on the Sciences in Islamicate Societies provides a comprehensive survey on science in the Islamic world from the 8th to the 19th century. Across six sections, a group of subject experts discuss and analyse scientific practices across a wide range of Islamicate societies. The authors take into consideration several contexts in which "science" was practiced, ranging from intellectual traditions and persuasions, to institutions such as courts, schools, hospitals, and observatories, to the materiality of scientific practices, including the arts and craftsmanship. Chapters also devote attention to scientific practices of minority communities in Muslim majority societies, and Muslim minority groups in societies outside the Islamicate world, thereby allowing readers to better understand the opportunities and constraints of scientific practices under varying local conditions. Through replacing Islam with Islamicate societies, the book opens up ways to explain similarities and differences between diverse societies ruled by Muslim dynasties. This handbook will be an invaluable resource for both established academics and students looking for an introduction to the field. It will appeal to those involved in the study of the History of Science, the History of Ideas, Intellectual History, Social or Cultural History, Islamic studies, Middle East and African studies including history, and studies of Muslim communities in Europe, South and East Asia"--